Social Support, Product Knowledge, Consumer Ethnocentrism, and Buying Decisions on Batik Products in Ponorogo East Java - Shabrina, Yuniar Nur; Santoso, Adi; Widhianingrum, Wahna (Universitas Batanghari Jambi, 2024)
This study aims to determine the effect of social support, product knowledge, and consumer ethnocentrism on buying decisions for Ponorogo batik in East Java. This research is quantitative. The number of samples in this study was 250, the sampling method used purposive sampling. The data collection method uses questionnaires distributed to respondents online and offline, data measurement uses a Likert scale of 1 – 5, the method of analysis of this research is SEM (Structural Equation Modeling) with the help of tools IBM SPSS AMOS statistics 26. The results of this study found that social support and consumer ethnocentrism had a positive and significant effect on increasing buying decisions, while product knowledge in this study was found not to have a significant effect on buying decision of batik clothes in Ponorogo. These findings contribute to the development of a customer culture theory regarding ethnocentrism towards local products that can become a culture in people's behavior as a love for the local products they have. The novelty of this research is that product knowledge is not a guarantee for someone to want to make a purchase. This is because consumers do not have sufficient information about the product, which results in consumers having limited knowledge.